(untitled) (Pedagogy of Higher and Secondary Education, 2022)
The prospects of professional preparation of teachers of fine art are examined in the article. On the basis of review of leading progress trends of modern higher education the ways of improvement of educational process are traced and the necessity of bringing of changes for the normative and methodical providing of speciality is grounded.